PCR Protocols - Park, Daniel J.; Park, Daniel J. (Methods in Molecular Biology, 2011)
Known for flexibility and robustness, PCR techniques continue to improve through numerous developments, including the identification of thermostable DNA polymerases which exhibit a range of properties to suit given applications. PCR Protocols, Third Edition selects recently developed tools and tricks, contributed by field-leading authors, for the significant value that they add to more generally established methods. Along with the cutting-edge methodologies, this volume describes many core applications, such as PCR cloning and sequencing, expression, copy number or methylation profile analysis, ‘DNA fingerprinting’, diagnostics, protein engineering, interaction screening as well as a chapter highlighting workflow considerations and contamination control, crucial for all PCR methods. Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary reagents and materials, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and up-to-date, PCR Protocols, Third Edition seeks to further elucidate this essential technique while also providing core principles with broad applications for scientists of all backgrounds.